Collaborative Management as a Catalyst for Artificial Intelligence Adoption in Elementary Education: A Case Study - Ridawati, Ridawati; Hidayat, Hidayat (Journal of Science and Education (JSE), 2026)
Islamic education institutions in Indonesia navigate a complex landscape, balancing the imperative to preserve spiritual-ethical values (adab) with the demand to foster critical, emancipatory consciousness for the 21st century. This tension is further complicated by rapid digital integration. This article employs a descriptive-narrative qualitative approach, synthesizing philosophical frameworks from Al-Attas, Freire, and Habermas with contemporary studies on institutional management. The analysis reveals that transformative leadership, utilizing strategic planning (e.g., SWOT), functions as a critical mediator. Findings indicate that successful integration models reframe digital technology not merely as an administrative tool but as a pedagogical space. This space must be infused with adab and ecopedagogical values to prevent dehumanization and alienation. This article proposes a synthesized framework of digital adab, which merges emancipatory goals with ethical-spiritual grounding, suggesting a pathway for holistic quality improvement and the cultivation of transformative 21st-century competencies.